2014
DOI: 10.1111/jam.12672
|View full text |Cite
|
Sign up to set email alerts
|

Photobacterium damselaesubsp.piscicidaresponds to antimicrobial peptides through phage-shock-protein A (PspA)-related extracytoplasmic stress response system

Abstract: To the best of our knowledge, this is the first report elucidating Phdp AMP-response mechanism using proteomics approach. AMP-responsive proteins identified in this study could serve as attractive targets for developing more effective antimicrobial agents against Phdp and other marine bacterial pathogens.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 31 publications
0
7
0
Order By: Relevance
“…Recently, we synthesized a class of cationic AMPs and studied their anti-bacterial activities, as well as their interactions with bacteria [ 25 29 ]. We showed that these synthetic AMPs exhibit high cytotoxicity against various cancer cells by inducing apoptosis [ 30 32 ].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, we synthesized a class of cationic AMPs and studied their anti-bacterial activities, as well as their interactions with bacteria [ 25 29 ]. We showed that these synthetic AMPs exhibit high cytotoxicity against various cancer cells by inducing apoptosis [ 30 32 ].…”
Section: Introductionmentioning
confidence: 99%
“…Evidence has suggested that AMPs are of greatest potential to represent such a new type of antibiotics [3][4][5]. We have designed and developed a series of cationic α-helical AMPs with potent activity and selectivity against a broad spectrum of Gram-negative and Gram-positive strains [12][13][14][15][16]. In our previous study, a potent AMP GW-Q6 exhibited potential antimicrobial activity against an MDR strain of Salmonella enterica serovar Choleraesuis [17].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, we have designed and synthesized a series of cationic and amphipathic α-helical AMPs with enhanced activity and selectivity against a broad spectrum of Gram-positive and Gram-negative strains [12]. According to our previous studies, our novel AMPs exhibited potent antibacterial efficacy against several marine pathogenic bacteria [13][14][15][16] and another important bacterial pathogen in pigs, Salmonella enterica serovar Choleraesuis [17]. However, it remains unknown whether AMPs possess antibacterial activity to combat multidrug-resistant (MDR) strains.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, recent findings described the presence of a pilus-like structure on the bacterial surface (Remuzgo-Mart ınez et al, 2014) and of cationic antimicrobial peptides (AMPs) (Tsai, Kuo, Lin, Lin, & Chen, 2015) as important mechanisms of Phdp pathogenicity.…”
Section: Introductionmentioning
confidence: 99%
“…The pathogenicity of Phdp is sustained by iron uptake mechanisms (Magarinos, Romalde, Lemos, Barja, & Toranzo, ), the presence of a polysaccharide capsular material (López‐Dóriga, Barnes, dos Santos, & Ellis, ) and the capability to produce an exotoxin effective against host macrophages and neutrophils (do Vale et al., ). In addition, recent findings described the presence of a pilus‐like structure on the bacterial surface (Remuzgo‐Martínez et al., ) and of cationic antimicrobial peptides (AMPs) (Tsai, Kuo, Lin, Lin, & Chen, ) as important mechanisms of Phdp pathogenicity . Rapid diagnosis of fish photobacteriosis is essential for a proper management and effective control of outbreaks in farmed fish (Andreoni & Magnani, ).…”
Section: Introductionmentioning
confidence: 99%